The effect of web-based self-monitoring to increase on-task behavior and academic accuracy of high school students with autism. Issue 3 (4th May 2020) - Romans, Sara K.; Wills, Howard P.; Huffman, Jonathan M.; Garrison-Kane, Linda
Abstract: Individuals with Autism Spectrum Disorders (ASD) often demonstrate behaviors that impair their school experiences. Therefore, the implementation of research-based strategies that will foster success for students with ASD is critical. The purpose of this study was to investigate the effect of a web-based self-monitoring application, I-Connect, designed to increase student on-task behavior and academic accuracy in a high school setting. An ABAB design was employed with two high school students diagnosed with ASD. I-Connect resulted in an immediate increase in on-task behaviors and academic accuracy in pre-algebra concepts. A functional relation between I-Connect and written expression was not identified. Web-based self-monitoring applications to promote autonomy and independence are discussed with recommendations for future research.